Ensino de história na escola pública: percursos e práticas de currículo(s) no ensino fundamental. Uberlândia-MG. (2010-2016) - Costa, Artur Nogueira Santos e (2017)
This research attends to the history area's curricular organization of elementary and middle school at the state public schools in Uberlandia-MG, from 2010 to 2016. It comprehends the curriculum as a historical movement controlled by real people - teachers, students, specialists -, on a shared field: the concrete public schools. The route of this research consists in a discussion based on different kinds of materials, such as legal texts, guidelines and basic curricular contents, combined with empirical observation methodology and oral history, all of them considered as evidences of the multiple constitutive layers of the curricular organization process. Therefore, from the articulation between these evidences, it analyzes what do the curriculums express in terms of values and practices.